2018
DOI: 10.1161/strokeaha.118.022740
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stroke in a General Male Population

Abstract: Background and Purpose— To further improve preventive strategies against stroke, there is a need for epidemiological long-term studies. The study aimed at a prospective investigation of stroke determinants in the general male population. Methods— During a period of 48 years, from 50 to 98 years of age, a population-based sample of 854 men was followed using repeated medical examinations, lifestyle questionnaires, data from hospital records and the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Atrial fibrillation was more common among stroke patients in the univariable analysis but not in the multivariable analysis. This is somewhat surprisingly, since atrial fibrillation is considered to be the strongest risk factor for stroke . The reason for this might be the fact that atrial fibrillation often leads to more severe strokes, which are more likely to be correctly diagnosed by the EMS.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation was more common among stroke patients in the univariable analysis but not in the multivariable analysis. This is somewhat surprisingly, since atrial fibrillation is considered to be the strongest risk factor for stroke . The reason for this might be the fact that atrial fibrillation often leads to more severe strokes, which are more likely to be correctly diagnosed by the EMS.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the standardized incidence rate of stroke increases by 13.19% annually in China. Besides, the disease characteristics of stroke in China have changed with the changing social environment and epidemiological survey reports have shown that the onset age of stroke presents a younger trend, especially in southwest China, where the age of stroke onset is significantly earlier [ 2 ]. According to the World Health Organization (WHO) data, the number of stroke patients in China will increase from 1.8 million in 2010 to 5.4 million in 2030 [ 3 ], indicating that young and middle-aged residents have become a potential population of stroke in China.…”
Section: Introductionmentioning
confidence: 99%
“…We cannot rule out that socioeconomic factors might have influenced seeking hospital care pattern. Another limitation is that we have not studied risk factor load over time with different analyses such as in an earlier study on men [ 18 ]. Further, we cannot rule out that repeated examinations over long time may have affected the women’s awareness of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study in Swedish women showed an inverse association between risk of stroke and years of education [ 24 ] compatible with our study. In a population study of men born 1913 followed for 48 years, low education was strongly associated with stroke [ 18 ]. Our study showed a strong association between education and stroke whilst SEP did not show any association.…”
Section: Discussionmentioning
confidence: 99%